Perinatal Depression of Exposed Maternal Women in the COVID-19 Pandemic in Wuhan, China - Sun, Guoqiang; Wang, Qi; Lin, Ying; Li, Ruyan; Yang, Lijun; Liu, Xian; Peng, Min; Wang, Hongyan; Yang, Xuewen; Ren, Wei; Yang, Hui; Cheng, Yao (Frontiers in Psychiatry, 2020)
Objective This study aims to investigate perinatal depressions of maternal women who gave birth to babies during the COVID-19 pandemic in Wuhan, and to evaluate effect of the pandemic on the perinatal depression prevalence. Methods A cross-sectional investigation was conducted to women hospitalized for delivery in Hubei Maternity and Child Healthcare Hospital from 31 Dec. 2019 to 22 Mar. 2020, a period across the whole process of COVID-19 pandemic in Wuhan. The Edinburgh Postnatal Depression Scale (EPDS) was adopted to evaluate perinatal depression status. Chi-square test and logistic regression model were mainly utilized for data analysis. Results A total of 2,883 participants were included, 33.71% of whom were rated to suffer depressive symptoms. In details, 27.02%, 5.24%, and 1.46% were designated as mild, moderate, and severe depressive symptoms, respectively. The perinatal depression prevalence increased along with the worsening COVID-19 pandemic. Compared to the 31 Dec. 2019-12 Jan. 2020 period, perinatal depression risk significantly decreased within the 3 weeks of 2-22 Mar. 2020 (1st week: OR = 0.39, 95% CI: 0.20, 0.78; 2nd week: OR = 0.35, 95% CI: 0.17, 0.73; and 3rd week: OR = 0.48, 95% CI: 0.25, 0.94); and the postnatal depression risk significantly elevated within the 4 weeks of 27 Jan.-23 Feb. 2020 (1st week: OR = 1.78, 95% CI: 1.18, 2.68; 2nd week: OR = 2.03, 95% CI: 1.35, 3.04; 3rd week: OR = 1.48, 95% CI: 1.02, 2.14; and 4th week: OR = 1.73, 95% CI: 1.20, 2.48). Conclusions The dynamic change of perinatal depression associates with the COVID-19 pandemic progress among the pandemic exposed maternal women. Elevated risk of postnatal depression was observed during the COVID-19 pandemic.